(untitled) (International Journal of Engineering and Computer Science, 2018)
Detection of learning difficulties among school children is a topic of research as predicting human behavior is a challenge for entire research community by taking this concern the study aims at predicting and classifying Dyscalculia among primary school children. Basically by following the approach of positive psychology towards learning detecting and designing intervention program for learner is a crucial aspect which actually requires targeted investigation so that right child should get the right help. In the present study we have used three classifiers rule-PART, J48 and SMO to predict the different classes of Dyscalculia